Hubungan Peran Keluarga Sebagai PMO (Pengawasan Minum Obat) dengan Kepatuhan Pengobatan Penderita Hipertensi di Puskesmas Miroto - Rahmadani, Azmi; Suryani, Yustina Indah; Luthfiah, Nita Tiara (Sultan Agung Islamic University of Semarang, 2025)
Background: Hypertension is one of the categories of Non Communicable Disease that has a high morbidity and mortality rate every year and is commonly experienced by those in the productive age group. Hypertension generally occurs without symptoms, which is why it is categorized as The Silent Killer or The Silent Disease. According to Riskesdas data (2018), hypertension cases in Indonesia account for 37% with a total death toll of 427,218 cases. The prevalences of hypertension in Central Java is at 37.57%. In Semarang City, the prevalence ranks first, with cases reaching 19.56%. Miroto Health Center is ranked 17th in hypertension cases among 37 districts in Semarang City, with 5,050 cases recorded in the 2022 NCD recap data of the health centers in the city. Factors that contribute to uncontrolled blood pressure in hypertension include age, educational background, lifestyle, medication adherence, and blood pressure control. Based on research by Laili et al., (2022), it was found 32.3% of hypertension patients didn’t routinely take their medication, which is part of 34.1% of hypertension sufferers. Non-adherence to medication worsens the patient's condition, prolongs treatment, and increases the risk of death. Therefore, hypertension can be controlled through medication adherence efforts, with the family playing a role as the Medication Adherence Supervisor (PMO). Methods: The research design used is quantitative correlational research with a cross-sectional approach. The number of samples in this study was 34. Results: The results of the research study showed that was a strong relationship between PMO (Medications Adherence Supervision) on medications adherence in hypertensions patients at Miroto Health Center. Conclusion: The role of the family as a PMO at Miroto Community Health Center influences medication adherence in hypertension patients. The involvement of the family as a PMO at Miroto Community Health Center shows a strong correlation with medication adherence in hypertension patients.